More than loss of taste and smell: burning watering eyes in coronavirus disease 2019 - Rokohl, Alexander C. (Clin Microbiol Infect, 2020)
OBJECTIVES: To evaluate ocular symptoms in European non-hospitalized patients with severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2) and to investigate associations with the demographic data as well as nasal and general physical symptoms. METHODS: In this prospective, observational study, 108 non-hospitalized patients with PCR-confirmed SARS-CoV-2 infection not requiring intensive care were asked about disease-associated ocular symptoms, demographic data, as well as general physical and nasal symptoms using a standardized questionnaire. Total ocular symptom score (TOSS) was evaluated during and, retrospectively, before development of coronavirus disease 2019 (COVID-19). Associations between TOSS and demographic data as well as general and nasal symptoms were evaluated. RESULTS: Seventy-five of the 108 COVID-19 patients (69.4%) had at least one ocular symptom during COVID-19. The most common symptoms included burning sensations in 39 (36.1%), epiphora in 37 (34.3%) and redness in 28 (25.9%), compatible with conjunctivitis. These symptoms occurred 1.96 ± 3.17 days after the beginning of COVID-19 and were mild. TOSS was significantly higher during COVID-19 (1.27 ± 1.85) than before the infection (0.33 ± 1.04; p < 0.001). There were no significant associations between TOSS and gender (β coefficient –0.108; p 0.302), age (–0.024; p 0.816), rhinorrhoea (–0.127; p 0.353), nasal itching (–0.026; p 0.803), sneezing (0.099; p 0.470), nasal congestion (–0.012; p 0.930), cough (–0.079; p 0.450), headache (0.102; p 0.325), sore throat (0.208; p 0.052), or fever (0.094; p 0.361). CONCLUSIONS: Ocular involvement in European non-hospitalized individuals with COVID-19 seems to be highly underestimated. Overall, these ocular symptoms, including burning sensations, epiphora and redness, seem to be mild and to not need treatment.